The new Latin American left : utopia reborn - Barrett, Patrick S.; Chavez, Daniel; Rodríguez Garavito, César A. (Pluto Press, 2008)
It was widely predicted that the end of the Cold War would lead to a prolonged period of US-friendly neo-liberal hegemony in Latin America. In fact, the left has re-emerged as a serious political actor. Today, leftist or 'progressive' political forces are in government in nine Latin American nations, and social movements continue to challenge neo-liberalism in several other countries. This book is a comprehensive study of the wide variety of leftist governments, parties and movements in the region, including Argentina, Bolivia, Brazil, Colombia, Mexico, Uruguay and Venezuela. It is essential for students of Latin American politics, political theory, social movements and international relations.